A modified Currency Demand Function and the Malaysian shadow economy: evidence from ARDL bounds testing approach - Awadh Ahmed Mohammed Gamal (Tanjong Malim, 2019)
A modified Currency Demand Function and the Malaysian shadow economy: evidence from ARDL bounds testing approach by Awadh Ahmed Mohammed Gamal